Performance Determinants in Immigrant Entrepreneurship: An Empirical Study - Rosique-Blasco, Mario; Madrid-Guijarro, Antonia; García-Pérez-de-Lema, Domingo (Senate Hall, 2017)
The purpose of this paper is to analyse the determinants of performance of businesses created by immigrants. An empirical study is carried out in the Spanish context, based on information obtained from 182 immigrant entrepreneurs. The immigrants come from African, Latin American and European countries. The results show that social capital, human capital and pull motivation to set up the company are positively associated with the performance of immigrant companies, whereas obstacles to social integration and difficulties in accessing financial resources are negatively related with performance. Additionally, the results show that Latin American and African immigrant entrepreneurs show lower performance than their European counterparts. These results have important economic and social implications that allow governments to improve the entrepreneurial ecosystem for the immigrant entrepreneurs.
Keywords: immigrant entrepreneurship|performance|human capital|social capital